Nonlinear optoacoustic readings from diffusive media at near-infrared wavelengths - Malekzadeh-Najafabadi, Jaber; Prakash, Jaya; Ntziachristos, Vasilis (Journal of Biophotonics, 2018)
Optoacoustic (photoacoustic) imaging assumes that the detected signal varies linearly with laser energy. However, nonlinear intensity responses as a function of light fluence have been suggested in optoacoustic microscopy, that is, within the first millimeter of tissue. In this study, we explore the presence of nonlinearity deeper in tissue ( 4 mm), as it relates to optoacoustic mesoscopy, and investigate the fluence required to delineate a switch from linear to nonlinear behavior. Optoacoustic signal nonlinearity is studied for different materials, different wavelengths and as a function of changes in the scattering and absorption coefficient of the medium imaged. We observe fluence thresholds in the mJ/cm2 range and preliminary find that different materials may exhibit different nonlinearity patterns. We discuss the implications of nonlinearity in relation to image accuracy and quantification in optoacoustic tomography.
CRIS-Team Scopus Importer:2023-03-08
Keywords: nonlinearity; optical imaging; optical parameters; optoacoustic (photoacoustic) imaging